2020
DOI: 10.2478/mgrsd-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of heat stress in 2015 and 2018 summer seasons in the region of the Lower Silesia (Poland)

Abstract: The main goal of this paper was to assess the intensity of heat stress in Lower Silesia, Poland, during selected weather events characterized by high air temperatures. The complex impact of weather on the thermal load of the human organism is presented using the Universal Thermal Climate Index (UTCI). The analysis was carried out for the 2015 and 2018 summer seasons and compared with the multiannual period of 1971–2018. It was based on meteorological data from the IMGW-PIB stations of Wrocław, Jelenia Góra and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…In the cold season, slight, moderate, and strong cold-stress categories were predominant. Similar conditions are typical for the regions located in the lowlands and the lower mountain zones of Poland and Central Europe [10,23,48,50,51,53,54,[66][67][68][69][89][90][91]. The analysis carried out in the paper showed that the frequency of moderate heat stress in July and August in the lower hypsometric zones of Kłodzko Land was about 5% lower than in the Carpathian region, confirming the results of the previous studies [48].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In the cold season, slight, moderate, and strong cold-stress categories were predominant. Similar conditions are typical for the regions located in the lowlands and the lower mountain zones of Poland and Central Europe [10,23,48,50,51,53,54,[66][67][68][69][89][90][91]. The analysis carried out in the paper showed that the frequency of moderate heat stress in July and August in the lower hypsometric zones of Kłodzko Land was about 5% lower than in the Carpathian region, confirming the results of the previous studies [48].…”
Section: Discussionsupporting
confidence: 87%
“…Such similarities were also noticed for cold-stress categories. However, it should be emphasized that the highest parts of the Sudetes Mountains are characterized by a very high number of days with extreme cold stress and no heat stress occurrence [52,[67][68][69]. In the discussed region, such conditions may be observed in the summit zone of theŚnieżnik Massif and the Bystrzyckie Mountains, which are the highest ridges in Kłodzko Land.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations